Laser land levelling technology for enhancing the productivity - Chaudhary, V P; Patel, Anurag (Indian Farming, 2018)
Laser levelling of agricultural land is a recent resource-conservation technology. It has the potential to change the way food is produced by enhancing resource-use efficiency of critical inputs without any disturbing and harmful effects on the productive resilience of the ecosystem. In spite of several direct and indirect benefits derived from laser land levelling technology, it is yet to become a popular farming practice in the developing and the underdeveloped countries. For accelerating its popularization and large-scale adoption, it requires a number of well-considered and synchronized research, extension, participatory, economic and policy initiatives keeping in view the long-term sustainability of our production systems. Popularization of this technology among farmers in a participatory mode on a comprehensive scale, therefore, needs appropriately focused attention on priority basis along with requisite support from researchers and planners. The change in our vision of future agriculture in relation to food and nutritional security, environmental safety and globalization of markets demands improving resource-use efficiency considerably to reach the desired growth levels in food production and agricultural productivity. Laser levelling is evidently one of the ways by which we can address these issues to a great extent.